STUDI PENAMBAHAN UNSUR Ca PADA PADUAN BINER Mg-Ca TERHADAP PEMBENTUKAN FASA DAN KOROSI IN-VITRO UNTUK APLIKASI IMPLAN MAMPU LURUH [Study of Calcium Addition in Mg-Ca Binary Alloy in Phase Transformation and in- Vitro Corrosion For Biodegradable Implant] - Lestari, Franciska Pramuji; Annur, Dhyah (Jurnal Metalurgi, 2015)
Magnesium alloy is currently being developed for biomedical devices application due to its biodegradable and biocompatible properties. In this study, Mg- Ca (1% wt, 4%wt, and 7%wt Ca) alloys have been been prepared through powder metallurgy process to study the effect of Ca addition to the phase transformation and the corrosion properties. Phase transformation were characterized through X-Ray Diffractometry (XRD). Meanwhile, the corrosion properties were evaluated in- vitro by means of polarization potentiodinamic in Hank’s solution. The electrochemical tests were carried out at room temperature using a corrosion measurement system. It was shown that Ca addition affect the formation of Mg,Ca phase which systematically could increase the corrosion rate and reduce potential corrosion of Mg- Ca alloy. From XRD evaluation, it can be seen that Mg,Ca phase were formed at Mg-7Ca alloy. The electrochemical testing also indicated the increasing of corrosion rate and the reduction of potential corrosion along with Ca addition were caused by formation of Mg,Ca phase which was more cathodic. This phenomena had shown that Mg-I Ca alloy could be studied further as a raw material for biodegradable implant application.